2003
DOI: 10.1021/ic020621o
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Reactivity of a Chromium(V) Glutathione Complex1

Abstract: Chromium(V) glutathione complexes are among the likely reactive intermediates in Cr(VI)-induced genotoxicity and carcinogenicity. The first definitive structure of one such complex, [Cr(V)O(LH(2))(2)](3)(-) (I; LH(5) = glutathione = GSH), isolated from the reaction of Cr(VI) with excess GSH at pH 7.0 (O'Brien, P.; Pratt, J.; Swanson, F. J.; Thornton, P.; Wang, G. Inorg. Chim. Acta 1990, 169, 265-269), has been determined by a combination of electrospray mass spectrometry (ESMS), X-ray absorption spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 97 publications
10
117
1
Order By: Relevance
“…Similar lines in the g = 5 region have been reported following the reduction of Cr(VI) by GSH [53]. We observed broader lines in this region following extended incubation of Cr(III) with GSH ( Fig.…”
Section: Esr For Cr(iii)supporting
confidence: 88%
See 4 more Smart Citations
“…Similar lines in the g = 5 region have been reported following the reduction of Cr(VI) by GSH [53]. We observed broader lines in this region following extended incubation of Cr(III) with GSH ( Fig.…”
Section: Esr For Cr(iii)supporting
confidence: 88%
“…Levina et al [53] reported a similar spectrum for GSH plus Cr(VI) at pH 7.0, and for a Cr(V)-GSH complex dissolved in water for two min. Their signal for the Cr(V)-GSH complex (g = 1.996) diminished by 7 min as the GSH-Cr(V) complex decomposed, whereas the intensity of the g = 1.986 signal increased [53]. They reported that all ESR signals from this Cr(V)-GSH complex disappeared after 10 min, indicating instability in aqueous solution.…”
Section: Generation Of the G = 1985 Cr(v) Signalmentioning
confidence: 75%
See 3 more Smart Citations